Peran Kepemimpinan Digital Dalam Meningkatkan Kinerja Organisasi Pendidikan: Literature Review - Syarqowi, Muhammad; Zuhaery, Muhammad; Hidayati, Dian (Universitas Negeri Yogyakarta, 2025)
This study aims to analyze the role of digital leadership in improving the performance of educational organizations through a systematic literature review. The research method used a literature review approach with a focus on articles related to digital leadership and improving the performance of educational organizations. The literature search was conducted through the Scopus database using the Publish or Perish application with the keywords